Inflammation and Wnt Signaling: Target for Immunomodulatory Therapy? - Jridi, Imen; Canté-Barrett, Kirsten; Pike-Overzet, Karin; Staal, Frank J. T. (Frontiers in Cell and Developmental Biology, 2021)
Wnt proteins are highly conserved glycoproteins best known for their role in development, cell fate specification, tissue regeneration and tissue homeostasis. Aberrant Wnt signaling is linked to developmental defects, malignant transformation and carcinogenesis, as well as to inflammation. Increasing lines of evidence recently demonstrated that a dysregulated activation of Wnt signaling is involved in the pathogenesis of chronic inflammatory diseases such as neuroinflammation, cancer mediated inflammation and metabolic inflammatory diseases. Recent findings highlighted the role of Wnt in the modulation of inflammatory cytokine production, in innate defense mechanisms, as well as in the bridging of innate and adaptive immunity. This sparked the development of novel therapeutic treatments against inflammatory diseases based on Wnt modulation. Here, we summarize the role and function of the Wnt pathway in inflammatory diseases, and focus on Wnt signaling as underlying master regulator of inflammation that can be therapeutically targeted.